2019
DOI: 10.1007/s00408-019-00270-z
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Mortality in Patients with Idiopathic Pulmonary Fibrosis: A US Cohort Study

Abstract: PurposeIn patients with idiopathic pulmonary fibrosis (IPF), hospitalizations are associated with high mortality. We sought to determine in-hospital mortality rates and factors associated with in-hospital mortality in patients with IPF.MethodsPatients with IPF were identified from the Premier Healthcare Database, a representative administrative dataset that includes > 20% of hospital discharges in the US, using an algorithm based on diagnostic codes and billing data. We used logistic regression to analyze asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 34 publications
9
28
1
Order By: Relevance
“…[35] The in uence of comorbid conditions and interventions on IPF mortality has been increasingly studied over the last decade. [23] Our study supports the ndings of others who have shown age, sex [30,[36][37][38], race and smoking history [36,37,39] to confer differential mortality risk. We found that admission to an academic center was associated with higher mortality risk, which is similar to previous studies [34] and may re ect a higher acuity of illness.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[35] The in uence of comorbid conditions and interventions on IPF mortality has been increasingly studied over the last decade. [23] Our study supports the ndings of others who have shown age, sex [30,[36][37][38], race and smoking history [36,37,39] to confer differential mortality risk. We found that admission to an academic center was associated with higher mortality risk, which is similar to previous studies [34] and may re ect a higher acuity of illness.…”
Section: Discussionsupporting
confidence: 89%
“…These ndings are supported by others using the NIS dataset, who reported similar all-cause mortality in patients with IPF admitted to the hospital 2006 to 2012 [29] and others using a similar dataset, who reported IPF mortality during index admission from 2011 and 2014 to be 10.3%. [30] These ndings stand in contrast to those published using the online CDC national death certi cate database, which showed IPF-related mortality to be increasing over this timeframe. [31,32] Besides, others reported decline in IPF all-cause mortality and hospitalizations using NIS dataset.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…[6][7][8] The studies mentioned above, however, did not use the current definition of AE-IPF in their inclusion criteria, and in addition, one study included patients treated in the ICU, 8 which is known to be a risk factor for death, at least in patients with IPF. 28 The other published studies concerning AE-FILD have been conducted in Japan, [9][10][11][12][13][14] of which only one demonstrated longer survival of patients with non-IPF compared with that of IPF 13 ; in another study, the prognosis of AE-IPF compared with other FILDs was even better. 9 Altogether, it can be stated that the earlier publications focusing on acute respiratory worsening or AE of IPF or non-IPF FILDs have consisted of small and heterogenic study populations with variable inclusion criteria, which complicate making comparisons between the investigations.…”
Section: Discussionmentioning
confidence: 98%
“…Improving outcomes in interstitial lung disease patients mechanically ventilated in the ICU Alexandre Demoule focused on outcomes and treatment strategies for interstitial lung disease (ILD) patients in the ICU. "We can only improve" was the take home message as the mortality of ILD patients exceeds 50% [97], with mechanical ventilation as a primary risk factor [98]. NIV and HFNC are scarcely explored and should not delay intubation.…”
Section: Modulation Of Drive: Ecco 2 Rmentioning
confidence: 99%